Strategi Komunikasi Humas J&T Express Bener Meriah - Fandi Gusti Mulyawan; Zulkifli Abdurrahman Usman (Sadida Islamic Communications and Media Studies, 2021)
This article examines the public relations strategy of J&T Express in maintaining customer loyalty. This article uses a qualitative methodology with a descriptive analysis method. The data was obtained by means of field observations and interviews with informants, the findings of this article are that J&T Express seems to be implementing exclusive strategies so that some customers are loyal for a long time. Public Relations J&T Express applies both internal and external strategies. The internal communication strategy includes a push strategy, in which the company's internal parties use a SWOT analysis to identify the industry's position with competitors. The external strategy includes a pull strategy, where J&T takes advantage of the COD feature that can attract consumers to minimize fraud by online shops